Credit and investment banking in Ukraine : current state and prospects of development - Kolodizev Oleg M.; Vlasenko Nataliya M. (Bìznes Inform, 2013)
The purpose of this paper is the study of the current state of credit and investment banks in Ukraine, identify gaps of its operation and prospects of further operation. As a result of the analysis, it was found that as of today the scale of investment in bank lending does not meet the needs of the productive sector of the economy in financial resources, despite the rather significant lending capacity of the banking system of Ukraine. The study indicated the main reasons hindering the development of credit and investment banks in Ukraine, which include macroeconomic and individual factors. It has been proposed a number of areas for development, the implementation of which will increase the level of participation of banks in the investment process. Prospects for further research on this subject can act to improve the mechanism of investment lending and development of new models for assessing investment risks in terms of different economic actors.